Relationship between soil chemical properties and rice yield under multiple stresses in the coastal agricultural land of Pangandaran, Indonesia - Nasrudin Nasrudin; Budiastuti Kurniasih; Eka Tarwaca Susila Putra; Eko Hanudin; Elisa Azura Azman (Universitas Sebelas Maret, 2025)
Seawater intrusion causes salinity and waterlogging in the coastal agricultural land of Pangandaran, Indonesia. Both limiting factors cause a decrease in soil chemical properties. The decline in rice yield occurred due to the low soil chemical properties. The study aims to identify the soil’s chemical properties based on limiting factors and to reveal its relationship with rice productivity in the coastal agricultural land of Pangandaran. Soil sampling was conducted using a purposive sampling method, and the samples were analyzed in the laboratory. Various soil properties are grouped into three clusters using hierarchical clustering. The cluster of waterlogging high salinity has very high Na-exchangeable with EC ranging from 0.21 - 4.93 dS m-1, while the other two clusters contain high Na-exchangeable and EC ranging from 0.101 - 0.581 dS m-1. Rice productivity under waterlogging-low salinity is <1 t ha-1, no waterlogging-low salinity is 3.63 t ha-1, and waterlogging-high salinity is 2.48 t ha-1. There are negative correlations between Na-exchangeable, water depth, and duration of waterlogging to rice yield (R2= -0.33; R2= -0.58; R2= -0.90). Multiple stresses cause limiting factors, and low soil chemical properties can inhibit plant development. The presence of waterlogging-low salinity has a strong impact on decreasing rice yield. Finally, our study provides an overview of the coastal agricultural land of Pangandaran based on multiple stresses. Furthermore, improved soil properties are needed with good management techniques to make it suitable for rice cultivation.